'New China' or 'New America'?: The American media myth of 'new China', 1911–1913. Issue 2 (3rd April 2019) - Guo, Yi
Abstract : This article examines the American-mediated myth of 'new China' spanning from the Chinese Revolution in 1911 to the American recognition of the Chinese Republic in 1913, in an effort to understand the complicated relations between news discourse, cultural issues and foreign relations in this particular historical context. The Chinese Revolution, overthrowing a deep-rooted feudalism and establishing an Americanized republican government, appealed to American sentiments of religious sympathy and ethnocentrism during the Progressive Era. The media myth of 'new China' was not only a significant part of discourses which enhanced American identity and nationalism, but also acted as the cognitive context and a determinant reason in the political discourse towards recognizing China.